2018
DOI: 10.2298/abs170616026n
|View full text |Cite
|
Sign up to set email alerts
|

Differences in bioactivity of three endemic Nepeta species arising from main terpenoid and phenolic constituents

Abstract: Methanol extracts of three endemic Nepeta species were analyzed for their main secondary metabolites, terpenes and phenolics, and further investigated for antioxidant capacity and embryonic toxicity in zebrafish. UHPLC/DAD/(±) HESI-MS/MS analysis showed that the dominant compound in N. rtanjensis was trans,cis-nepetalactone, the cis,trans isomer of this monoterpene lactone was dominant in N. sibirica, while nepetalactone was detected only in traces in N. nervosa. In all investigated species, rosmarinic acid wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
3
2
Order By: Relevance
“…As we know, there are no literature data on the antioxidant potential of N. cyrenaica extracts and EO. However, there are several studies dealing with the antioxidant effects of other Nepeta taxa, 1,4,17,53,60,66,69 In contrast to the results of Zengin et al 4 and Patial et al, 60 the results of the current study showed that the extract obtained with DCM as the least polar solvent had the highest antioxidant capacity.…”
Section: Antioxidant Activitycontrasting
confidence: 98%
See 3 more Smart Citations
“…As we know, there are no literature data on the antioxidant potential of N. cyrenaica extracts and EO. However, there are several studies dealing with the antioxidant effects of other Nepeta taxa, 1,4,17,53,60,66,69 In contrast to the results of Zengin et al 4 and Patial et al, 60 the results of the current study showed that the extract obtained with DCM as the least polar solvent had the highest antioxidant capacity.…”
Section: Antioxidant Activitycontrasting
confidence: 98%
“…In general, Sharma et al 7 reported that more than 20 phenolic acid derivatives were isolated from the Nepeta species. The values presented in Table 4 were lower than in the studies performed by Dienaitė et al 59 and Nestorović Živković et al 66 These authors found that rosmarinic acid, ferulic acid, caffeic acid, and chlorogenic acid were the most abundant phenolic components of analysed Nepeta species. Rosmarinic acid was identified as one of major phenolic constituents of N. baytopii , while ferulic acid was not detected.…”
Section: Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…Phenolic compounds, α-tocopherol and ergosterol all possess antioxidant activity [24,[29][30][31] and are found in higher concentrations in the extracts of mature fruiting bodies; however, many other unknown metabolites are probably involved. Although phenolics may prevent lipid peroxidation [32], lipophilic compounds such are tocopherols and ergosterol may show a greater effect in the β-carotene bleaching assay.…”
Section: Samplementioning
confidence: 99%